Knowledge and practice on road traffic rules among Sri Lankan Transport Board bus drivers in Jaffna - Abishanth, T.; Jahan, H.; Senanayake, A.M.S.S .; Thaakshajini, R.; Samarasinghe, S.D.N.P.; Parameswaran, N.; Kandeepan, K. (University of Jaffna, 2024)
Background and objective: According to the World Health Organization world life expectancy 2020 report, Sri Lanka has reached 4200 deaths by road traffic accidents annually. As accidents mainly affect the earning population, they create a significant economic burden. Road traffic accidents are mostly predictable and can be prevented with good road safety interventions and technologies. This study aimed to assess the knowledge and practice on road traffic rules among Sri Lanka Transport Board (SLTB) bus drivers in Jaffna district. Methods: A descriptive cross-sectional study was conducted among SLTB drivers in Jaffna district. The study period was November 2022 to February 2023, and the sample size was 216. Knowledge and practice of the drivers were measured by a self- administered questionnaire which was content and face validated. Data were processed and analysed by using SPSS software. Chi square test and ANOVA test were used to determine the associations. Results: In total, 216 SLTB drivers participated in our study with a response rate of 93.05%. Mean age of the sample was 42.8 years. A significant association was found between drivers’ knowledge and practice of road traffic rules (p<0.001). Knowledge of road traffic rules was significantly associated with the age at getting a heavy vehicle (p=0.014). Knowledge about road signs was significantly associated with the educational level of the driver (p<0.001) and the experience range of driving (p=0.036). Practicing road traffic regulations was also associated with the age at getting a heavy vehicle license (p<0.001). Conclusion and recommendations: Significant associations were found between knowledge and practice regarding road traffic rules. All the drivers agreed they follow road signs and significant association is obvious between knowledge about road signs and experience of driving. Proper interventions would help to reduce the risky behaviour of drivers and ensure the safety of passengers. We have suggested to assess the drivers' knowledge periodically and arrange awareness programmes to maintain drivers’ knowledge and practice at an appropriate level.
Keywords: Knowledge; Practice; Road traffic accident; Bus drivers